Peer reviewing – a responsibility and a power of the university? - Smedsrød, Bård; Reierth, Eirik; Moksness, Lars; Longva, Leif (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. Journal coordinated peer reviewing, a hallmark of scholarly publishing, is also a pivotal part of other central academic processes, such as evaluation of research grant applications, and ranking of applicants for faculty/research positions. Hence, journal coordinated peer reviewing may be viewed as “the mother of academic peer reviewing”. On this background, it is astonishing that universities and other public R&D institutions take only a very limited interest in the management and policy shaping of this cornerstone of scholarly publishing. We suggest that the universities need to become more aware of the pivotal role of the peer reviewing jobs carried out by their professors and researchers. The peer reviewing should be viewed as a partial, in kind payment from the institutions involved to the journal publishers. The advantages of this are manifold: i) negotiating power that may lead to easier and quicker implementation of open access publishing and/or ii) reducing costs, in particular the unjustifiably high subscription and licensing rates set by the big commercial publishing houses; iii) better control of how scientific staff use their time for the good of the university; iv) managing a unified policy shaping of peer reviewing, reducing fraud and flaws. This will in turn increase quality of the research produced by the universities. The EU has recently announced their goal of making all European scientific articles freely accessible by 2020. This announcement was made unanimously by the EU ministers responsible for research and innovation. The ministers have not announced what means to use in achieving their announced goal. We suggest a united approach whereby taking control of the peer review job could be an interesting road to follow. Such a unified international action among universities and grant agencies would be very beneficial in order to make the changes needed to establish peer reviewing as a truly academically based responsibility. The increasing international agreements and actions to implement open access publishing are indications that such changes are possible. By standing together universities will be able to break the economic grip that the big commercial publishing houses have on academic research. Some may argue that it is the right of each individual scientist to decide on the extent and for what journal to perform peer reviewing. However, if an employer for some reason limits the amount of time used to do peer reviewing for certain commercial publishing houses, it would not interfere with the academic freedom to do research and to choose freely where and how to publish. After all, work contracts include instructions on how to perform a certain amount of teaching, administration and research. The option of directing where to do or not to do peer review should not be very controversial. By taking control of and organizing peer reviewing universities would obtain a means to regain the academic freedom that was lost when commercial enterprises took over the society driven journals, introducing heavy paywalls. And it may facilitate a development towards an open science regime.